JUSTICE AND COMPENSATION FOR LAND ACQUISITION FOR COMMUNITIES AFFECTED BY INFRASTRUCTURE DEVELOPMENT - Gloria Gita Putri Ginting; Henry Aspan; Ari Prabowo; Etty Sri Wahyuni (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the fairness of land acquisition compensation for communities affected by infrastructure development in Indonesia. The main focus of the study is to examine the gap between normative provisions mandating "fair and just" compensation and the reality of implementation on the ground, as well as to identify factors that often cause communities to feel disadvantaged in the land acquisition process. This study uses a juridical-normative method strengthened by an empirical approach. Data were collected through a literature review of laws and regulations, court decisions, and related policy documents, as well as in-depth interviews with affected communities, government officials, and land appraisers at several national strategic project locations. The results show that although the legal framework has regulated the principle of fairness, its implementation still faces various obstacles, including unclear assessment standards, weak transparency and community participation, limited appraisal resources, and minimal assistance for vulnerable groups. Fairness in compensation is not simply measured by nominal values; it must include procedural, distributive, and restorative justice. This study recommends the need for more measured regulatory reformulation, strengthening institutional capacity, and a transformative approach that prioritizes the recovery of the socio-economic conditions of affected communities, so that infrastructure development truly brings prosperity without leaving anyone behind.